A phase II/III randomized clinical trial of CisPlatin plUs Gemcitabine and Nabpaclitaxel (GAP) as pReoperative chemotherapy versus immediate resection in patIents with resecTable BiliarY Tract Cancers (BTC) at high risk for recurrence: PURITY study - Monica Niger; Federico Nichetti; Lorenzo Fornaro; Chiara Pircher; Federica Morano; Federica Palermo; Lorenza Rimassa; Tiziana Pressiani; Rossana Berardi; Andrea Casadei Gardini; Elisa Sperti; Lisa Salvatore; et al. (BMC Cancer, 2024)
Abstract Background Biliary tract cancers (BTCs) are rare and lethal cancers, with a 5-year survival inferior to 20%(1–3). The only potential curative treatment is surgical resection. However, despite complex surgical procedures that have a remarkable risk of postoperative morbidity and mortality, the 5-year survival rate after radical surgery (R0) is 20–40% and recurrence rates are up to ~ 75%(4–6). Up to ~ 40% of patients relapse within 12 months after resection, and half of these patient will recur systemically(4–6). There is no standard of care for neoadjuvant chemotherapy (NAC) in resectable BTC, but retrospective reports suggest its potential benefit (7, 8). Methods PURITY is a no-profit, multicentre, randomized phase II/III trial aimed at evaluating the efficacy of the combination of gemcitabine, cisplatin and nabpaclitaxel (GAP) as neoadjuvant treatment in patients with resectable BTC at high risk for recurrence. Primary objective of this study is to evaluate the efficacy of neoadjuvant GAP followed by surgery as compared to upfront surgery, in terms of 12-month progression-free survival for the phase II part and of progression free survival (PFS) for the phase III study. Key Secondary objectives are event free survival (EFS), relapse-free survival, (RFS), overall survival (OS), R0/R1/R2 resection rate, quality of life (QoL), overall response rate (ORR), resectability. Safety analyses will include toxicity rate and perioperative morbidity and mortality rate. Exploratory studies including Next-Generation Sequencing (NGS) in archival tumor tissues and longitudinal ctDNA analysis are planned to identify potential biomarkers of primary resistance and prognosis. Discussion Considering the poor prognosis of resected BTC experiencing early tumor recurrence and the negative prognostic impact of R1/R2 resections, PURITY study is based on the rationale that NAC may improve R0 resection rates and ultimately patients’ outcomes. Furthermore, NAC should allow early eradication of microscopic distant metastases, undetectable by imaging but already present at the time of diagnosis and avoid mortality and morbidity associated with resection for patients with rapid progression or worsening general condition during neoadjuvant therapy. The randomized PURITY study will evaluate whether patients affected by BTC at high risk from recurrence benefit from a neoadjuvant therapy with GAP regimen as compared to immediate surgery. Trial registration PURITY is registered at ClinicalTrials.gov (NCT06037980) and EuCT(2023–503295-25–00).